ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERAWAT GIGI DALAM PELAKSANAAN KEGIATAN UKGS (USAHA KESEHATAN GIGI SEKOLAH) DI PUSKESMAS WILAYAH DINAS KESEHATAN KABUPATEN BANDUNG - Nining Ningrum; Laksmono Widagdo; Sutopo Patria Jati (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEAnalysis of factors influencing dental nurse performances in UKGS program among Puskesmas in public health department of Bandung DistrictABSTRACTIn Bandung District data showed that many students suffer from bleeding gums, dental caries in students tend to rise nearly 90% in elementary school students, the average incidence of dental caries occur in the age group 6-12 years with DMF-T = 2,7. Where as the target of Healthy Indonesia 2010 on caries incidence is not more than two. Not optimal oral health care in children aged 6-12 years (primary school age), showed that the performance of dental nurses in UKGS care services was not optimal.This study was an explanatory research with cross sectional approach. Data were collected by interview and observation. The number of samples is 50 dental nurses.The results showed that the performance of dental nurses in the implementation of the District Health Office UKGS in Bandung is only about 58.0% and that have a good performance is only 42.0%. Variables that are directly related to the performance of dental nurses in the implementation of UKGS are training, knowledge and motivation The variables most affect the dental nurse performance of the implementation UKGS was training (RP 20.931) means that dental nurse with a good level of 21 times likely to have a better performance compared to the dental nurse with less knowledge, and the most influential factor was training. Means that dental nurses who have high training will have 21 times better performance compared with dental nurses with low training in the implementation of UKGS. Key words : Performance, dental nurse at implementation, UKGS